Mixed bipolar direct current (DC) transmission system - TANG GENG; XUE YINGLIN; XU ZHENG (2013)
The invention discloses a mixed bipolar DC transmission system. The system comprises a rectification converter station and an inversion converter station which are connected through a DC transmission line, wherein the rectification converter station is formed by two thyristor converters through serial connection, and the serial connection node is grounded; and the inversion converter station is formed by two modular multilevel converters (MMCs) through serial connection, the serial connection node is grounded, and positive and negative ends after serial connection are connected with one-way connection power devices. The system has the advantages of low cost and loss, high reliability and the like of the existing thyristor converter, flexible control of the MMCs, low harmonic, active-reactive power decoupling control, low dependence on an alternating current system and the like; and the system is divided into positive and negative poles, so that operating reliability is strengthened, and the power devices prov